The role of psychology and communication skills in orthodontic practice: a systematic review - Martin Baxmann; Zoltán Baráth; Krisztina Kárpáti (BMC Medical Education)
Abstract Effective communication and psychological strategies are integral to orthodontic practice, influencing patient satisfaction, adherence, and overall treatment outcomes. This systematic review, conducted in accordance with PRISMA guidelines and registered with PROSPERO (ID: CRD42024560432), examined the role of these strategies in orthodontic care and their integration into educational curricula. A comprehensive search identified studies focusing on communication and psychological interventions in orthodontics. The findings emphasize that patient-centered communication enhances understanding, adherence, and satisfaction. Structured approaches, such as personalized follow-up reminders and digital tools like social media, have shown significant improvements in patient engagement. Psychosocial factors, including anxiety and body image concerns, were identified as critical barriers to adherence, necessitating tailored psychological support and empathy-based communication. Additionally, gaps in orthodontic education were identified, with recommendations for integrating simulations, interprofessional education, and ongoing training into curricula to address these challenges. This review underscores the importance of addressing the psychological and communicative dimensions of orthodontic care, providing actionable recommendations for enhancing patient outcomes and optimizing educational practices. Future research should explore the long-term impact of these strategies and assess their effectiveness across diverse populations.